(untitled) (Physical Education, Health and Social Sciences, 2025)
The China-Pakistan Economic Corridor (CPEC), the most prominent and strategically significant component of China’s Belt and Road Initiative (BRI), occupies a contested position at the intersection of high-stakes geopolitical diplomacy and deeply opaque infrastructure governance. This study interrogates the dual character of CPEC by examining two interconnected dimensions: the structural governance deficits embedded in the Gwadar Deep Seaport Agreement, and the layered geopolitical calculations that have shaped Pakistan’s sustained commitment to the corridor. With respect to the first dimension, the study brings into critical focus the terms of the port concession, paying particular attention to the asymmetric 91-9 revenue-sharing arrangement between the China Overseas Port Holding Company (COPHC) and the Gwadar Port Authority (GPA), and to the systematic exclusion of local and provincial stakeholders from the project’s governance architecture. These transparency failures raise substantive concerns about sovereign debt sustainability, economic equity, and the long-term viability of a development model that has largely bypassed established parliamentary accountability mechanisms. With respect to the second dimension, the study examines the strategic imperatives driving Pakistan’s engagement with CPEC—imperatives that extend well beyond the project’s developmental framing to encompass energy security, maritime strategic depth, and the pursuit of a counterbalancing alignment with Beijing in a regional environment shaped by deepening US-India convergence. The study concludes that whilst CPEC retains substantial transformative potential for Pakistan’s infrastructure and industrial base, persistent information asymmetries and structurally imbalanced contractual conditions pose a serious and underappreciated risk to the corridor’s long-term legitimacy, both domestically, in the communities most directly affected, and regionally, in the broader context of South Asian geopolitical stability.